FAITH MARKETING A THEORETICAL ARTICLE (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
now a days in India there is a tremendous growth of those organizations which are connecting their consumable products with the religion. India is a country of multicultural, multifaith, a cluster of different customs, language etc.The purpose of this paper is to elucidate its reader in general and to the marketers and organizations as a whole on faith marketing.In a society overrun by commercial clutter, religion has become yet another product sold in the consumer market. Faiths of all kinds must compete not only with each other, but with auncountable of more enjoyable and more suitable leisure activities. The researcher tries to shows how religious branding has expanded over the past few decades in India to create a mixed world of commerce and faith where the holy becomes secular and the secular holy. Organizations dealing in faith marketing are having a tremendous growth in few years.The paper is also an attempt to establish the theoretical demarcation of the term faith marketing. The term faith marketing has caused controversy. There are two streams: that of the theologians, on one hand and that of the marketers, on the other hand.  Marketers have their own view regarding the application of marketing into the faith sphere. The article tries to emphasise the necessity to adapt the religious organizations activities and the ways they must be presented to the society’s actual characteristics. This can be achieved by using appropriate marketing tools and methods; however, the particularities of religion must be taken into account in order not to alter its faith values.